Pengolahan Limbah Organik Domestik Menjadi Pupuk Kompos Skala Rumah Tangga Di Desa Wisata Sukunan - Muhammad Rivaldy Hafrizia; Dodit Ardiatma (DPPM Universitas Pelita Bangsa, 2022)
Domestic waste is the biggest contributor to environmental pollution, both air, water and soil pollution. One of them is organic solid waste generated from household activities so that it must be processed in order to reduce environmental pollution. Organic waste processing can be done by composting or processing organic waste with certain media into compost that can be used by farmers for agricultural activities as fertilizer. This process can be carried out on a small scale or household scale as a community efficiency measure to reduce environmental pollution. The purpose of this practical work is to find out the process of managing domestic organic waste into compost. The data collection technique was carried out by conducting interviews and collecting primary and secondary data and observing field conditions. Various methods such as methods of sorting, processing, reusing waste to form compost that produces economic value and is supported by the application of simple technology used so as to maximize performance and operations in the handling and management of household waste. Keywords : Domestic Waste, Organic Waste, Compost